Functional roles of RNAi in C. elegans - Miska, Eric (Henry Stewart Talks, 2007)
Small non-coding RNA pathways, Genetics of RNAi, MicroRNAs, RNAi screening, Biological roles of RNAi, Systemic RNAi in C. elegans
Reviewed at 2020/09/10